Influence of the pre-treatment of nanofibers obtained from mushrooms on the mechanical properties of the paper - Zin, Mizan Izzati Mat; Suratem, Muhammad Azammuddin; Nawawi, Wan Mohd Fazli Wan (Polimery, 2021)
The influence of the pre-treatment process (freezing, drying) on the tensile properties of chitin paper obtained from nanofibers of three commercial species of fungi: oyster mushrooms (P. ostreatus), enoki (F. velutipes) and shiitake (L. edodes) was investigated. The chitin nanofibers were extracted by a mild alkaline process. The highest tensile strength was observed for paper obtained from fresh mushrooms fibers, which may result from the lack of the chitin fiber modification. Freezing and drying processes have been found to reduce the strength of the paper, possibly due to ice crystal formation and the keratinization effect of the nanofibers, respectively. The paper obtained from enoki fungus nanofibers was characterized by the highest tensile strength, which may be due to the very long fiber. However, in terms of elongation at break, the best results were obtained with oyster mushrooms nanofibers, probably due to the relatively shorter chitin fiber. The long enoki nanofibers can therefore be used as a good reinforcement of the paper.